Exploring EFL Classroom Interactions in An Online Setting: A Case Study in Indonesia - Abdusyukur, Muhammad Rafi (SALEE: Study of Applied Linguistics and English Education, 2024)
The COVID-19 pandemic has transformed the form of interaction in the EFL classroom in Indonesia. Consequently, it is vital for Indonesian EFL teachers to analyse the current form of interaction in online settings to ensure quality teaching and learning. Even though many studies have addressed the issue, this study offers an alternative analysis by adapting FIACS (Flanders Interaction Analysis Category System) as one of the most common tools for classroom interaction analysis. This case study aimed to explore EFL classroom interaction by using FIACS as the framework. The necessary data was collected through direct and indirect observation between an EFL teacher and his lower secondary students. Based on the analysis, it appeared that the online EFL classroom interaction was dominated by the teacher. One of the causes was the passiveness of the students due to the technological glitches. The pattern and characteristics of the interaction also changed. One of the most notable changes was the difficulty to observe and manage the interaction between students. These observed features of the EFL online classroom portrayed how the class is conducted as well as ideas for other EFL teachers and practitioners to prepare and organize it.